Climatic and geomorphic drivers of plant organic matter transport in the Arun River, E Nepal - Hoffmann, Bernd; Feakins, Sarah J.; Bookhagen, Bodo; Olen, Stephanie M.; Adhikari, Danda P.; Mainali, Janardan; Sachse, Dirk (Earth and planetary science letters, 2016)
Fixation of atmospheric CO2 in terrestrial vegetation, and subsequent export and deposition of terrestrial plant organic matter in marine sediments is an important component of the global carbon cycle, yet it is difficult to quantify. This is partly due to the lack of understanding of relevant processes and mechanisms responsible for organic-matter transport throughout a landscape. Here we present a new approach to identify terrestrial plant organic matter source areas, quantify contributions and ascertain the role of ecologic, climatic, and geomorphic controls on plant wax export in the Arun River catchment spanning the world's largest elevation gradient from 205 to 8848 m asl, in eastern Nepal. Our approach takes advantage of the distinct stable hydrogen isotopic composition (expressed as δD values) of plant wax n-alkanes produced along this gradient, transported in river waters and deposited in flood deposits alongside the Arun River and its tributaries. In mainstem-flood deposits, we found that plant wax n-alkanes were mostly derived from the lower elevations constituting only a small fraction (15%) of the catchment. Informed by remote sensing data, we tested four differently weighted isotopic mixing models that quantify sourcing of tributary plant-derived organic matter along the Arun and compare it to our field observations. The weighting parameters included catchment area, net primary productivity (NPP) and annual rainfall amount as well as catchment relief as erosion proxy. When weighted by catchment area the isotopic mixing model could not explain field observations on plant wax δD values along the Arun, which is not surprising because the large arid Tibetan Plateau is not expected to be a major source. Weighting areal contributions by annual rainfall and NPP captured field observations within model prediction errors suggesting that plant productivity may influence source strength. However weighting by a combination of rainfall and catchment relief also captured the observed δD value pattern suggesting dominantly erosive control. We conclude that tributaries at the southern Himalayan front with high rainfall, high productivity, high relief and high erosion rates dominate plant wax exports from the catchment. •We modeled OM sourcing within the trans-Himalayan Arun River catchment.•OM exported by the Arun is dominantly derived from its lower elevated tributaries.•Highest OM export was observed where dense vegetation coincides with strong erosion.